2013
DOI: 10.1097/qai.0b013e318291f331
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Infection of Female Genital Tract Tissue for Use in Prevention Studies

Abstract: Objective Ex vivo HIV-1 challenge has been proposed as a bio-indicator of microbicide product effectiveness. The objective of this study was to establish optimal parameters for use of female genital tract tissue in this model. Design Ex vivo challenge involves in vivo product use, followed by tissue biopsy, and exposure of the tissue to HIV-1 in the laboratory. Methods Paired ectocervical and vaginal biopsies were collected from 42 women and 28 had additional biopsies from each site collected after 5% lido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 23 publications
2
31
1
Order By: Relevance
“…56 No difference in p24 antigen production between FOL and LUT phases p24 antigen production from tissue biopsies or explants after ex vivo infection by HIV-1 BaL has been used as a model for early mucosal HIV infection in women and as an exploratory safety endpoint in phase I studies of potential vaginal or rectal HIV microbicides. 38,40,57,58 In contrast to other investigators, we found that vaginal tissue produced significantly more p24 antigen than ectocervical tissue. When the samples were analyzed separately, in combination (unadjusted p-value, Table 2), or in combination controlling for race, contraceptive/sexual practices, and tissue source (adjusted p-value, Table 2), we found no significant differences in p24 antigen production between FOL and LUT phases.…”
Section: No Differences In Vaginal Ph or Nugent Score Between Fol Andcontrasting
confidence: 56%
See 1 more Smart Citation
“…56 No difference in p24 antigen production between FOL and LUT phases p24 antigen production from tissue biopsies or explants after ex vivo infection by HIV-1 BaL has been used as a model for early mucosal HIV infection in women and as an exploratory safety endpoint in phase I studies of potential vaginal or rectal HIV microbicides. 38,40,57,58 In contrast to other investigators, we found that vaginal tissue produced significantly more p24 antigen than ectocervical tissue. When the samples were analyzed separately, in combination (unadjusted p-value, Table 2), or in combination controlling for race, contraceptive/sexual practices, and tissue source (adjusted p-value, Table 2), we found no significant differences in p24 antigen production between FOL and LUT phases.…”
Section: No Differences In Vaginal Ph or Nugent Score Between Fol Andcontrasting
confidence: 56%
“…38,39 For the analyses of p24 antigen production, categorization of infected versus not infected samples was done using 0.1 log steps and a Boolean method, followed by comparison of infected versus not infected samples by Fisher's exact test or McNemar's statistic as appropriate. 40 Log transformation of the antimicrobial data could not be performed because some of the data points were negative numbers.…”
Section: Hiv-1 P24 Antigen Production From Ectocervical or Vaginal Timentioning
confidence: 99%
“…Therefore, many pathogenesis studies (42)(43)(44) did not use the polarized model, supporting the use of the immersion model herein. Importantly, the immersion model allows for the use of small amounts of mucosa derived from survival biopsy specimens, similar to what is being done in pharmacodynamic studies in humans (45).…”
Section: Discussionmentioning
confidence: 99%
“…The tissue PK/PD assessment in clinical trials represents a challenge as only 1 to 2 ectocervical and vaginal biopsy specimens can be collected from participants (3). A recent study defined female genital tract tissue collection procedures for use in the ex vivo challenge assays (49). These approaches are being evaluated in ongoing clinical trials (41).…”
Section: Discussionmentioning
confidence: 99%